Self-degradation temporary suffocating agent and preparation method thereof - HUANG KAI; LIU JIANBIN; ZHOU ZHIXIANG; QIU YING; ZHANG YALONG; WANG ZONGZHEN; DU HENGYI; LIU SHUN; DANG TIANXING (2023)
The invention relates to the technical field of petroleum and natural gas extraction, and discloses a self-degradation temporary suffocating agent and a preparation method thereof. The self-degradation temporary suffocating agent is prepared from the following raw materials: 0.5 to 2 parts of activated cellulose, 10 to 18 parts of acrylamide, 0.01 to 0.04 part of cross-linking agent, 0.1 to 3 parts of auxiliary agent, 0.1 to 0.6 part of initiator and 90 to 110 parts of water. The preparation method of the self-degradation temporary suffocating agent comprises the following steps: S1, adding cellulose into a sodium hydroxide aqueous solution, stirring for 4-6 hours at 70 DEG C, filtering, and washing with water until the pH value is 7-8 to obtain activated cellulose; s2, dissolving the activated cellulose and acrylamide in water, stirring, heating to 70 DEG C, adding a cross-linking agent, reacting for 5 minutes, adding an auxiliary agent, reacting for 5 minutes, adding an initiator, stirring, and stopping sti